Синтез оптимального послекорреляционного измерителя параметров источников излучения в беспроводных сетях - Епишкин, С. А. (Проблеми телекомунікацій, 2010)
In the article contain's the synthesis of the optimal maximum likelihood algorithm aftercorrelation measure the parameters of radiation sources in wireless networks, different path difference between the points of reception and Doppler frequency.
Keywords: беспроводная сеть; допплеровская частота